2021
DOI: 10.1111/pbi.13705
|View full text |Cite
|
Sign up to set email alerts
|

ERF9 of Poncirus trifoliata (L.) Raf. undergoes feedback regulation by ethylene and modulates cold tolerance via regulating a glutathione S‐transferase U17 gene

Abstract: Summary Plant ethylene‐responsive factors (ERFs) play essential roles in cold stress response, but the molecular mechanisms underlying this process remain poorly understood. In this study, we characterized PtrERF9 from trifoliate orange (Poncirus trifoliata (L.) Raf.), a cold‐hardy plant. PtrERF9 was up‐regulated by cold in an ethylene‐dependent manner. Overexpression of PtrERF9 conferred prominently enhanced freezing tolerance, which was drastically impaired when PtrERF9 was knocked down by virus‐induced gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…In Poncirus trifoliata L. Raf., ethylene‐induced ERF transcription factor PtrERF9, plays a positive role in cold tolerance (Zhang et al., 2022). By contrast, ethylene negatively regulates cold tolerance in Medicago truncatula (Zhao et al., 2014) and A. thaliana (Shi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Poncirus trifoliata L. Raf., ethylene‐induced ERF transcription factor PtrERF9, plays a positive role in cold tolerance (Zhang et al., 2022). By contrast, ethylene negatively regulates cold tolerance in Medicago truncatula (Zhao et al., 2014) and A. thaliana (Shi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple GST genes in pumpkin are induced by cold environments [ 40 ]. PtrERF9 improves cold resistance by promoting the expression of PtrGSTU17 and reducing ROS content in trifoliate orange under cold stress [ 41 ]. Until now, GST genes involved in grape cold resistance have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IAA27 and SAUR71 was significantly upregulated in ‘SY’ under cold stress, indicating that they could be used as candidate genes for further research into the mechanism of auxin in regulating grape cold resistance. In recent years, an increasing number of studies have reported the important regulation effect of ERF in the cold resistance of fruit trees [ 41 , 48 , 52 , 53 ]. ERF genes involved in grape cold resistance have also been reported, including VaERF057 [ 54 ] and VaERF092 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter fragment of CmGLP2-5 was recombined to the pGreen 0800-LUC vector to generate the reporter. The constructs were co-transformed into tobacco seedlings as described in a previous report [ 69 ]. The transformed tobacco seedlings were cultured in the dark for 2 days to conduct a dual luciferase assay.…”
Section: Methodsmentioning
confidence: 99%